Aprendizajes a nivel plástico del carnaval de negros y blancos, en la licenciatura a través de la vivencia 2012- 2019 (2020)
The present document is an analysis of the knowledge and contributions made from the experience of the Carnaval de Negros y Blancos” to the pedagogical artistic processes and products carried out in the “Licenciatura en Educación Artística con Énfasis en Danza y Teatro”, directly from the plastic arts, taking into account the nature of this traditional Pasto party. to achieve this type of analysis, a brief inquirí will be made by concepts within the plastic arts and the history of Carnival. Coming to identify artistic forms present in this celebration in southern Colombia. From this information, we will go on to describe each artistic pedagogical product that students and teachers of the bachelor’s degree have managed to develop during their time in this program, And thus be able to make a comparison in thhe elements and knowledge present during the celebration of Carnival and the most relevant plastic processes that have been used in each artistc and pedagogical product. This study between 2012 and 2019, focuses on the knowledge and plastic elements learned in the Bachelor’s Degree, as well as its contribution to the completeness of the academic process in Art Education, not only seen from Dance and Theater. Offering an opinión from my experince whitin a process of plastic creation regarding the “Carnaval de Negros y Blancos”, in orden to provide an easy to read document with specific information on motives and creative processes